The Development of Module for Improving Computational Thinking Skills on Science Education based on Google Colaboratory - Silvi Putri Ayu Ningsih; Zainur Rasyid Ridlo (SEAMEO SEAMOLEC, 2024)
The purpose of this study was to analyze the module development process to improve skills for students in junior high school and then conduct a limited test on prospective teacher students. The development method used in this research is the ADDIE method by using analyzing the results of validation and limited testing using samples from prospective science teacher students, the purpose of using prospective teacher students as research samples because this module was developed for junior high school students, therefore prospective teacher students must understand the module developed before it is implemented to junior high school students. The results of module development resulted in a content validity value of 88.1%, science concepts 87.8%, Construct 94.7, Language 89.3%, layout 88.9%, on average the validity value of the module that has been developed reaches 89.7%, this indicates that the module developed is categorized as very valid and ready to use. Implementation of the module in a limited class resulted in an increase in the average value of posttest from 27.9 to 87.5 and resulted in an N-gain value of 0.82. based on these results it can be concluded that the developed module is able to direct and improve the ability to think computationally.